CHALLENGES AND METHODS FOR DEVELOPING PROFESSIONAL FOREIGN LANGUAGE FLUENCY IN UNIVERSITIES - Mashkhura Muzaffar Qizi, Nosirova; Zebiniso Xaydarovna, Xamrayeva (PT. Antis International Publisher, 2025)
acquisition tailored for employability purposes in educational institutions. It addresses the increasing need for specific terminologies, cultural practices, and communication etiquettes beyond general language mastery to prepare learners for professional contexts. Methods: The research employs quantitative methods to analyze instructional practices, such as communicative language teaching, role-play, narrating, and digital storytelling. These practices are evaluated for their effectiveness in addressing language-related challenges: language density, limited practice opportunities, cultural barriers, and students’ motivation. Results: Findings reveal that authentic, contextually related practices significantly enhance students’ oral competence and confidence in business discourse. Additionally, creating a welcoming and culturally responsive classroom atmosphere is crucial to overcoming fluency challenges and fostering effective learning outcomes. Novelty: This research highlights the importance of integrating language components into industry-specific training, focusing on improving business language accuracy and promoting intercultural competence. It offers practical insights for educators aiming to equip learners for careers in diverse multicultural environments.